2013
DOI: 10.1007/s11046-013-9709-1
|View full text |Cite
|
Sign up to set email alerts
|

Acremonium strictum: Report of a Rare Emerging Agent of Cutaneous Hyalohyphomycosis with Review of Literatures

Abstract: We present a case of cutaneous hyalohyphomycosis due to Acremonium strictum in an immunocompetent individual along with an overview of fungal infections caused by A. strictum. The diagnosis was confirmed by the presence of hyphae in microscopic examination of cutaneous biopsy and discharge, positive culture for A. strictum and sequencing of the isolate at reference centre. The infection resolved with itraconazole and terbinafine. Cutaneous or subcutaneous infections of A. strictum have rarely been reported. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 28 publications
0
19
0
1
Order By: Relevance
“…Traditionally, species of Sarocladium have been reported as plant pathogens or as saprobes ( Gams & Hawksworth 1975 , Chen et al 1986 , Helfer 1991 ). However, numerous recent studies have demonstrated that some might also be involved in human infections ( Das et al 2010 , de Hoog et al 2011 , Khan et al 2011 , Perdomo et al 2011 , Summerbell et al 2011 , Fernández-Silva et al 2013 , Júnior et al 2013 , Sharma et al 2013 ). Specifically, the new species described here, i.e., S. bifurcatum , S. hominis , S. pseudostrictum and S. subulatum , were isolated from human samples.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, species of Sarocladium have been reported as plant pathogens or as saprobes ( Gams & Hawksworth 1975 , Chen et al 1986 , Helfer 1991 ). However, numerous recent studies have demonstrated that some might also be involved in human infections ( Das et al 2010 , de Hoog et al 2011 , Khan et al 2011 , Perdomo et al 2011 , Summerbell et al 2011 , Fernández-Silva et al 2013 , Júnior et al 2013 , Sharma et al 2013 ). Specifically, the new species described here, i.e., S. bifurcatum , S. hominis , S. pseudostrictum and S. subulatum , were isolated from human samples.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 14 cases of Acremonium/Sarocladium superficial infections are reported in the literature, 9 of them being cutaneous 11,32,[88][89][90][91][92][93][94] and 5 subcutaneous, 33,34,[95][96][97] although the identity of the fungus only was molecularly confirmed in one case (A strictum Four patients were immunocompromised by the administration of corticosteroids for severe chronic pulmonary disease 91 or kidney transplantation, 88,89,97 but only one patient succumbed due to the infection. 91 The clinical features showed by these patients comprised erythematous and ulcerated skin, 34 painless swelling, 97 redness and pain, 88 swollen skin with extensive necrotic areas, pustules and purulent exudate, 32,91,92 ulceration, 90 erythematous and scaly plaque, 11,94 nodules 33,95 and fistulae with seropurulent secretion.…”
Section: Cutaneous and Subcutaneous Infectionsmentioning
confidence: 99%
“…92 The anatomical sites affected differed among patients, and these were the face, 33 cheek, 34 thigh, 89 forearm, 91 ankles, 32 legs, 90,94 hand 92,97 or foot and hands. 11…”
Section: Cutaneous and Subcutaneous Infectionsmentioning
confidence: 99%
“…The fungus is a saprotroph commonly occurring in soil, in decaying plants, and mushrooms. Interestingly, in rare instances the fungus can turn pathogenic to humans [27].…”
Section: Kletno: Sztolnia Wiejąca and Sztolnia Turystycznamentioning
confidence: 99%